Biodiversity information retrieval across networked data sets - Sarinder, K.K.S.; Lim, L.H.S.; Merican, A.F.; Dimyati, K. (2010)
Purpose - Biodiversity resources are inevitably digital and stored in a wide variety of formats by researchers or stakeholders. In Malaysia, although digitizing biodiversity data has long been stressed, the interoperability of the biodiversity data is still an issue that requires attention. This is because, when data are shared, the question of copyright occurs, creating a setback among researchers wanting to promote or share data through online presentations. To solve this, the aim is to present an approach to integrate data through wrapping of datasets stored in relational databases located on networked platforms. Design/methodology/approach - The approach uses tools such as XML, PHP, ASP and HTML to integrate distributed databases in heterogeneous formats. Five current database integration systems were reviewed and all of them have common attributes such as query-oriented, using a mediator-based approach and integrating a structured data model. These common attributes were also adopted in the proposed solution. Distributed Generic Information Retrieval (DiGIR) was used as a model in designing the proposed solution. Findings - A new database integration system was developed, which is user-friendly and simple with common attributes found in current integration systems. Originality/value - The proposed system is unique in that it allows biodiversity data sharing, through the integration of biodiversity databases, hence enabling scientists to share information and generate knowledge. It also solves copyright problems by suggesting distributed warehouses, giving data owners the benefit of having their database under their own jurisdiction. It meets the requirements of querying heterogeneous and remote biodiversity databases.